The presentation and the outcome of penetrating abdominal bullet injuries – Iraqi hospital based study - Jarullah Abdullah , Fouad; Akram Abed, Bashar; Saleh Ibrahim, Nazar (Diyala Journal of Medicine, 2022)
Background: In Iraq penetrating injuries to the abdomen caused by firearm are more common than stab wounds with remarkable mortality and morbidity. Early recognition of the injuries and immediate treatment are mandatory in saving the lives of many of those patients. Objective: To review the presentation and evaluate the early post-operative morbidity and mortality of abdominal bullet injuries in Baghdad teaching hospital. Patients and Methods: This prospective study was conducted on 132 patients admitted to second surgical unit in Baghdad teaching hospital after sustaining bullet injury to the abdomen during the time period of one year from October 2013 to September 2014. Results: The most vulnerable age group involved, between 21-30 years comprised 71.2% of total. Male to female ratio was 43:1(male comprised 97.73%). It was observed that the majority of the injured patients were military personnel (83%), associated with high velocity missiles (81%). It was seen that 96.6% of patients had positive findings during laparotomy; small intestine was involved in the majority of the patients 42.6% followed by large intestine in 35.65%, then liver in 20.86%. Majority of the patients had involvement of two organs (42%), followed by one organ in (28%). The major postoperative complications were wound infection (28.6%), followed by chest infection in (24.4%). The major cause of death was septicaemia in 80%. Conclusion: Explorative laparotomy continues to be the most accurate method used to diagnose the presence of penetrating intra-abdominal injuries with a negative laparotomy rate of 3.4%. The mortality rate tended to be related to the number of intra-abdominal organs injuries; high rates of surgical site and chest infections were found and septicaemia was the chief cause of death after 48 hours. Hospital stays in our study were prolonged in comparison to other developed countries.